2020
DOI: 10.1109/tcst.2019.2891234
|View full text |Cite
|
Sign up to set email alerts
|

Fast Adaptive Observers for Battery Management Systems

Abstract: MIT~ibranes http://Ilibraries.mit-edu/ask DISCLAIMER NOTICE Due to the condition of the original material, there are unavoidable flaws in this reproduction. We have made every effort possible to provide you with the best copy available. Thank you. The images contained in this document are of the best quality available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 36 publications
(5 reference statements)
0
14
0
Order By: Relevance
“…The goal in either case is to determine conditions under which this convergence take place. These conditions are linked to properties defined as persistent excitation (PE) and uniform observability [128,129,66,130,131]. These PE properties are usually associated with the underlying regressor ω, and typically realized by choosing the exogenous signals such as r(t), the input into the reference model M appropriately, which the control designers have the freedom to select.…”
Section: Learning = Parameter Estimationmentioning
confidence: 99%
See 1 more Smart Citation
“…The goal in either case is to determine conditions under which this convergence take place. These conditions are linked to properties defined as persistent excitation (PE) and uniform observability [128,129,66,130,131]. These PE properties are usually associated with the underlying regressor ω, and typically realized by choosing the exogenous signals such as r(t), the input into the reference model M appropriately, which the control designers have the freedom to select.…”
Section: Learning = Parameter Estimationmentioning
confidence: 99%
“…Necessary and sufficient conditions for this convergence requires that the regressor ω be persistently exciting. Several results also exist in ensuring accelerated convergence of these estimates [162,163,131,164,159,165]) using matrix regressors, a time-varying learning rate for Γ, and dynamic regressor extension and mixing.…”
Section: Adaptive Observersmentioning
confidence: 99%
“…With an objective to relax the PE condition, a matrix regressor (MR) based adaptive observer for SISO LTI plants is designed, [19][20][21][22] where the notion of strong persistent excitation (S-PE) is introduced to obtain online computation of degree of persistence and leads to faster convergence. Recently, adaptive control architectures are introduced where the properties of finite excitation 23,24 are used for the convergence of parameter estimation error to zero.…”
Section: Introductionmentioning
confidence: 99%
“…From(22) and(23) it can be proved that w 1 (t), w 2 (t) ∈  ∞ . Thus, from(21) it can be shown that u where Y f is the upper bound of ||Y f || Proof. Since Y (t), Y f (t), θ(t) ∈  ∞ and from(17) it can be established that 𝜇(t) is exponentially decaying, it can be shown from (15) that x(t) ∈  ∞ .…”
mentioning
confidence: 99%
“…The underlying structure in many of the adaptive identification and control problems consists of a linear regression relation between two dominant errors in the system [4], [13], [14]. Examples include adaptive observers [15]- [19] and certain classes of adaptive controllers [1]. The underlying algebraic relation is often leveraged in order to lead to a fast convergence through the introduction of a time-varying learning rate in the parameter estimation algorithm, which leads to the wellknown recursive least squares algorithm [20].…”
Section: Introductionmentioning
confidence: 99%